THE DYNAMICS BETWEEN VULNERABILITY AND FAITH IN MARK 5:25-34: INSIGHTS FROM IGNATIAN PEDAGOGY - Dirgaprimawan, Bernadus; Ariyanto, Yohanes Ferry (Sanata Dharma University, 2024)
This article employs an exegetical approach to examine the story of a woman afflicted with a 12-year hemorrhage, who finds healing through her faith in Jesus. The objective is to identify the multifaceted vulnerabilities she confronts, encompassing the physical, emotional, cognitive, and social dimensions. Despite societal marginalization, her story challenges societal norms and religious laws, emphasizing her deep faith and the transformative impact of encountering Jesus. This study, informed by Ignatian pedagogy, focuses on the holistic understanding of human nature and on the character development of the woman in that story. The analysis illuminates the woman's profound physical affliction, emotional distress, cognitive challenges, and social marginalization. Furthermore, it investigates how her unwavering faith in Jesus transcends societal norms, leading to personal healing and maturity. The results highlight how faith and compassion can bring about significant changes, showing how Ignatian spirituality offers valuable insights into addressing vulnerability and encouraging empathy for those facing hardships in life.